Technology Absorption by Innovative SMEs : Knowledge Economy Forum VII, Ancona, Italy - World Bank (Universita Politecnica delle marche, Rome, and the World Bank, Washington, DC, 2013)
These proceedings highlight the key findings and public policy lessons that emerged from the Knowledge Economy Forum VII (KEF VII) on Technology Absorption by Innovative Small and Medium Enterprises, held in Ancona, Italy on June 17-19, 2008. Technology Absorption by Innovative Small and Medium Enterprises was the focal theme of the KEF VII held in Ancona, Italy on June 17-19, 2008. The Ancona Forum was the seventh in a series of flagship events organized by the Private and Financial Sector Development Department in the Europe and Central Asia Region of the World Bank (ECSPF). The 2008 Forum was organized to exchange experiences among global leaders, policymakers, academics and practitioners in ECA countries that can contribute to accelerating the transition to an increasingly knowledge-based economy.